2003
DOI: 10.1002/ddr.10319
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction by serine proteinases in astrocytes: Regulation of proliferation, morphologic changes, and survival via proteinase‐activated receptors

Abstract: Astrocytes, in addition to their conventionally known function as supporting cells in the brain, have recently been revealed to play a much more pivotal role in maintaining the brain's vitality than has been previously assumed. Astrocytes, an intimate partner of neurons, coordinate neuronal activity across cellular networks in the central nervous system (CNS). Proteinases like thrombin can act on astrocytes via activation of plasma membrane proteinase-activated receptors (PARs), thereby mediating cellular resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…The regional distribution of the neuronal lesions reflects that of the GluR distribution. Astrocytes with swollen perikarya and karyorrhexis have often been observed in the vicinity of these lesions [8][9]. It has been suggested that astrocytes contribute to a decline of neurologic function by either the accumulation and release of EAAs after ischemia and oxidative stress or by formation of epileptogenic scars in response to CNS injury and metabolism of protoxins to potent toxins.…”
Section: Introductionmentioning
confidence: 99%
“…The regional distribution of the neuronal lesions reflects that of the GluR distribution. Astrocytes with swollen perikarya and karyorrhexis have often been observed in the vicinity of these lesions [8][9]. It has been suggested that astrocytes contribute to a decline of neurologic function by either the accumulation and release of EAAs after ischemia and oxidative stress or by formation of epileptogenic scars in response to CNS injury and metabolism of protoxins to potent toxins.…”
Section: Introductionmentioning
confidence: 99%
“…PI-PLC d3 also has been identified in many histotypes at low concentrations [Pawelczyk and Matecki, 1998]; PI-PLC d4 is expressed in the brain as well as in regenerating tissues [Pawelczyk, 1999]; PI-PLC g1 is expressed in keratinocytes and foetal cartilage [Ananthanarayanan et al, 2002] and has been found almost exclusively in the cytoplasm [McBride et al, 1991;Diakonova et al, 1997]; also PI-PLC e occurs in many tissues [Wing et al, 2003]. Notwithstanding the growing interest for the role played by the PI-PLC family enzymes in the nervous system [Ledeen and Wu, 2004], no definitive studies have been accomplished in glial cells [Choi et al, 1989;Tallant and Higson, 1997;Wang and Reiser, 2003]. As a matter of fact the inositol lipid cycle seems to be involved in glial activation during neurodegenerative processes [Vitale et al, 2004].…”
mentioning
confidence: 99%
“…2005). In the nervous system, PAR‐2 is widely expressed in brain, spinal cord, and peripheral nerves (Wang and Reiser 2003a,b; Bushell et al. 2006).…”
mentioning
confidence: 99%